2011
DOI: 10.2174/156802611796904924
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of TRPV1 by Resiniferatoxin, from Preclinical Studies to Clinical Trials

Abstract: In primary sensory neurons, the capsaicin receptor TRPV1 functions as a molecular integrator for a broad range of seemingly unrelated chemical and physical noxious stimuli, including heat and altered pH. Indeed, TRPV1 is thought to be a major transducer of the thermal hyperalgesia that follows inflammation and tissue injury as this response is impaired in TRPV1-deficient mice. Following the molecular cloning of TRPV1 in 1997, over a dozen companies embarked on efforts to find clinically useful TRPV1 antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 87 publications
0
75
0
Order By: Relevance
“…Ingenol mebutate from Euphorbia peplus has recently been licensed for the treatment of the precancerous skin condition actinic keratosis and has also proven effective in the treatment of superficial basal cell carcinoma in phase IIa clinical trials (Siller et al, 2010). Resiniferatoxin, a tigliane diterpenoid from Euphorbia resinifera, is currently in phase I/II trials for the treatment of intractable pain (Kissin and Szallasi, 2011). Prostratin (a tigliane), which is produced by Homalanthus nutans, Euphorbia fischeriana, and Euphorbia cornigera, has shown potential as an adjuvant therapy for the treatment of latent HIV infection (Miana et al, 1985;Qing-Gao et al, 1997;Kulkosky et al, 2001;Johnson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ingenol mebutate from Euphorbia peplus has recently been licensed for the treatment of the precancerous skin condition actinic keratosis and has also proven effective in the treatment of superficial basal cell carcinoma in phase IIa clinical trials (Siller et al, 2010). Resiniferatoxin, a tigliane diterpenoid from Euphorbia resinifera, is currently in phase I/II trials for the treatment of intractable pain (Kissin and Szallasi, 2011). Prostratin (a tigliane), which is produced by Homalanthus nutans, Euphorbia fischeriana, and Euphorbia cornigera, has shown potential as an adjuvant therapy for the treatment of latent HIV infection (Miana et al, 1985;Qing-Gao et al, 1997;Kulkosky et al, 2001;Johnson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…7,8) A detailed biological study revealed that 1 is a potent activator of the ion channel, transient receptor potential vanilloid 1, in the plasma membrane of sensory neurons. 9,10) The strong analgesic property of 1 caused by desensitization of nociceptive neurons offers 1 as a potential therapeutic agent. Two other daphnanes, daphnetoxin 11,12) and trigohownin A, 13) have more highly oxidized carbon frameworks and a phenyl orthoester and display different bio-functions: daphnetoxin is a human immunodeficiency virus (HIV) inhibitor while trigohownin A exhibits cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to circumvent some of the issues with current TRPV1 antagonists, novel reversible or permanent interventional neuroablative therapies based on TRPV1 agonists are being explored [29,30]. Administration of a vanilloid agonist, such as capsaicin or its ultrapotent analog RTX [31], can cause calcium-induced cytotoxicity and lead to a TRPV1-selective axonopathy that spares surrounding non-TRPV1-expressing somatosensory proprioceptive afferent and motor efferent nerve fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Because TRPV1 agonists are painful initially upon application, in general, administration of a TRPV1 agonist necessitates pretreatment with a local anesthetic and, in the case of intrathecal administration, general anesthesia, which requires the patient to be either in the clinic or in the operating room. In addition, while capsaicin is effective when administered focally to treat Morton's neuroma or osteoarthritis [45] and RTX is effective when administered intrathecally to treat osteosarcoma [34], they generally cannot be given systemically in large doses since they produce a decrease in core body temperature and may be cardiotoxic, although there is a much larger safety margin for RTX [29]. Thus while some conditions may be amenable to local, interventional TRPV1 agonist administration, other pain conditions, where pain is more diffuse or delocalized, may not be appropriate candidates for treatment with localized therapies.…”
Section: Introductionmentioning
confidence: 99%